Numerical simulation of velocity field in a arteriouvenous fístula - A. Santos, Willyam B. (2019)
The objective of this study is to analyze the hemodynamic factors of flow in an arteriovenous fistula (AVF). The geometric model of the AVF is obtained virtually from a computed tomography. In the mathematical model, which simulates blood flow in the AVF, it is considered a non-Newtonian fluid, incompressible and transient laminar flow. The flow behavior in the AVF is given by the blood velocity in five points corresponding to the mass flow in the systolic phase and in the diastolic phase. The numerical simulation of the velocity field in the systolic phasepresented greater intensity of axial and radial recirculations. The presence of recirculations allows figurative elements to collide excessively in the wall of the endothelium